Painting - Henry, Sally (London : Franklin Watts, 2008)
Provides step-by-step instruction to create ten paintings by using poster paints and basic techniques, and discusses the required tools and materials, color mixing, perspective, and other related topics.
Self-portrait -- Simple still life -- My own room -- Landscape -- Dinosaur -- Figure painting -- Creatures -- Pop art posters -- House of wax -- Magic palace.
Includes index.
4.3
3-6.
3-6
Keywords: Painting -- Technique -- Juvenile literature; Painting -- Technique; Painting -- Technique